1995
DOI: 10.1093/clinids/21.6.1378
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Use of Erythromycin: Link to Increased Erythromycin Resistance in Group A Streptococci

Abstract: Resistance to erythromycin in group A streptococci has become an important problem among outpatients in Finland. The prevention of such problems requires information about the relationship between antimicrobial consumption and antimicrobial resistance. Having found considerable variation among health authority areas in the proportions of group A streptococci resistant to erythromycin, we investigated the potential impact of local differences in the consumption of this agent on the development of resistance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 23 publications
4
82
0
1
Order By: Relevance
“…Results of these studies overall revealed a remarkable variability of resistance rates at different times and in different epidemiological settings (for examples, see references 1, 8, 9, 11, 25, 31, 37, and 41). A clear relationship between resistance rates and the extent of macrolide usage in community medicine was also demonstrated, with relatively rapid variations of the former in response to modifications of prescription policies (6,11,30,31).Recently, increased macrolide resistance rates in clinical isolates of S. pyogenes have been reported in several countries (1,6,8,25). This phenomenon, which likely reflects the vast popularity of the last generation of macrolides (such as azithromycin, clarithromycin, and roxithromycin) in community medicine, is a cause of considerable concern for antimicrobial chemotherapy.…”
mentioning
confidence: 89%
“…Results of these studies overall revealed a remarkable variability of resistance rates at different times and in different epidemiological settings (for examples, see references 1, 8, 9, 11, 25, 31, 37, and 41). A clear relationship between resistance rates and the extent of macrolide usage in community medicine was also demonstrated, with relatively rapid variations of the former in response to modifications of prescription policies (6,11,30,31).Recently, increased macrolide resistance rates in clinical isolates of S. pyogenes have been reported in several countries (1,6,8,25). This phenomenon, which likely reflects the vast popularity of the last generation of macrolides (such as azithromycin, clarithromycin, and roxithromycin) in community medicine, is a cause of considerable concern for antimicrobial chemotherapy.…”
mentioning
confidence: 89%
“…During the past three decades, numerous reports have demonstrated a significant prevalence of erythromycin resistant S. pyogenes around the world (4-10). Furthermore, several reports have demonstrated that the increase in the incidence of erythromycin resistant S. pyogenes strains is related to increased macrolide consumption in the community (22)(23)(24)(25)(26). Macrolide antibiotics, especially new ones such as clarithromycin and azithromycin, are widely selected for the treatment of upper respiratory tract infections such as sore throat in our country.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%
“…Due to the observed erythromycin resistance rate, antibiotic prophylaxis among the recruits at the training sites was examined. No apparent correlation with erythromycin resistance and a history of erythromycin use at the sites was noted; however, other researchers have shown the reality of this concern (10,25).…”
Section: Vol 41 2003 Notes 4809mentioning
confidence: 82%